In Silico Characterization of Selected Carbohydrate Active Enzymes (CAZymes) from Malaysia's Unique Genome Assemblies through Genomic Data Mining - Miharil, Alvin Owen; Aisyah Mohamed Rehan, (Progress in Engineering Application and Technology, 2024)
In silico characterization of proteins helps to understand the structure and function of protein targets before experimental approaches. Carbohydrate-active enzymes (CAZymes) are enzymes that convert plant biomass into industrially valuable products like bioenergy and biofuel production. This study aims to perform in silico genomic data mining for CAZymes elucidation from selected genome assemblies isolated in Malaysia for industrial biotechnology. The National Center for Biotechnology Information (NCBI) database was used to investigate Malaysia's diversified genome assembly, discovering 1386 complete genomes. CAZymes from six bacterial genomes were identified and categorized, with two bacteria, Thermobifida fusca and Parageobacillus caldoxylosilyticus, chosen for further investigation. Three CAZymes from Thermobifida fusca were chosen for protein modelling due to their homology range to available protein structures. I-TASSER and ExPASy SWISS-MODEL protein modelling tools were used to fully characterize the structural and functional properties of these CAZymes. Future research should focus on refining tertiary models, conducting protein-ligand docking experiments, and molecular dynamics simulations to gain insights into their stability, flexibility, and functional mechanisms in a simulated physiological environment.